Soundscape co-governance for a healthy megacity - Dunhu Chang; Xinyue Chen; Yuxin Bai; Zhanfeng Dong (npj Urban Sustainability)
Abstract Megacities are increasingly confronted with diverse sources of noise pollution, which pose significant challenges to effective noise abatement. This paper employs the ‘Framework for Human Health Risk Assessment to Inform Decision Making’ and integrates residents’ self-assessed health impacts to replace traditional instrument-based noise measurements. The goal is to explore how soundscape co-governance can be encouraged as a strategy to manage noise in megacities. Using the Extended Theory of Planned Behavior, we analyze the contradiction between risk identification and risk solution, considering factors such as noise source, exposure, and sensitivity. Our findings indicate that non-industrial noise in megacities causes more severe health impacts, as assessed by residents, compared to industrial noise. However, public participation in soundscape co-governance is notably lower for non-industrial noise. Furthermore, residents living closest to noise sources, within 0–100 m, experience the most significant health impacts yet are the least active in participating in soundscape co-governance. Similarly, residents with higher education levels also experience greater health impacts from noise but are less active in participating in soundscape co-governance compared to others. The primary reason for this inconsistency between the health impacts on residents and their participation in soundscape co-governance is the reliance on the traditional environmental governance system. To enhance health-oriented soundscape co-governance in megacities, it is recommended to adopt community-based co-governance, implement refined governance strategies based on exposure levels, promote public integration and strengthen connections between the government and the public.